Media advocates, Latino citizens and niche cable. - Wible, Scott (Cultural Studies, 2004)
In Shot in America , Chon Noriega calls for the study of media activism's work 'within the system' of state institutions and for analysis of the relationships between media activism, the television industry and government policies. This article uses a cultural policy studies focus to answer this call and map the deregulated terrain upon which media advocacy groups must now operate. Liberal governance demands that media advocates find means other than state-directed appeals to advance their agendas. As such, this essay examines the efforts of several Latino advocacy groups to garner viewer support for a Latino-themed cable television show, Resurrection Boulevard , and to use the series as a vehicle for increased Latino participation in the television industry. This article focuses on the issue of access for Latinos to professional positions that affect television programming, and it presents tools for advocacy efforts within political spheres to achieve more socially equitable access to media technologies. First, the paper traces the regulatory history of the broadcasting and cable television industries to show how the federal government narrowly conceives of 'the public interest' as a specifically consumerist one. The article then analyses the structures that led to cable television's 'narrowcasting' format, such as Showtime's 'No Limits' programming, and argues that liberalism has created a context wherein several media advocates normalise the 'citizen-consumer' model. Having established this groundwork, the author then conducts a case study of the economic and social forces that shape Resurrection Boulevard , which is written, produced and acted by Latinos. Through this study, the author maintains that advocacy groups' consumer-based appeals to Latinos as 'citizen-consumers' fail to serve as effective instruments for achieving increased minority representation in the television industry.